THE INFLUENCE OF GREEN INTELLECTUAL CAPITAL, GREEN INNOVATION AND ECO EFFICIENCY ON SUSTAINABLE PERFORMANCE - Eka Sari; Holiawati; Suripto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This research aims to examine the influence of green intellectual capital, green innovation and eco- efficiency on sustainability performance. This research is classified as associative quantitative research. The type of data used is secondary data obtained from www.idx.co.id and the company website. The population in this research is the Sri- Kehati Company which is registered on the IDX for the 2019 - 2023 period. The sample for this research was determined using a purposive sampling method so that 20 samples companies were obtained. The analytical method used is Panel Data Model Regression analysis. The results of this research shows that green intellectual capital, green innovation and eco- efficiency have an effect on sustainability performance, green intellectual capital has an effect on sustainability performance, green innovation has no effect on sustainability performance and eco efficiency has no effect on sustainability performance.